PRINCIPLES OF ORGANIZING RUSSIAN LANGUAGE LESSONS IN UZBEK GROUPS OF ACADEMIC LYCEUMS BASED ON MODERN TEACHING METHODS - Gulsara Akhmedovna Ruzibaeva (International Journal of Literature and Language Studies, 2026)
The article examines the organization of Russian language teaching in Uzbek groups of academic lyceums through modern pedagogical technologies. The didactic potential of communicative, competency-based, interactive, and digital approaches in teaching Russian as a second language is analyzed. Particular attention is paid to the development of students' communicative competence through problem-based learning, project activities, cooperative methods, and digital educational resources. Based on pedagogical practice and experimental results, the study identifies key principles for improving the effectiveness of Russian language lessons in academic lyceums. The findings demonstrate that the implementation of modern teaching methods contributes to the development of language skills, increased student motivation, and improved quality of language education.